CO2 sequestration by methanogens in activated sludge for methane production. (15th March 2015) - Mohd Yasin, Nazlina Haiza; Maeda, Toshinari; Hu, Anyi; Yu, Chang-Ping; Wood, Thomas K.
Highlights: Methane (CH4 ) produced stems from CO2 sequestration by methanogens. Enriched methanogens from WAS was dominated by an active archaeal community. CO2 which has a single carbon atom is a profitable resource for energy production. Abstract: Carbon dioxide (CO2 ) is the main greenhouse gas; hence, processes are needed to remove it from the environment. Here, CO2 was used as the substrate to generate methane (CH4 ) by using enriched methanogens after anaerobic enrichment of waste activated sludge (WAS); therefore, we demonstrate that methanogens from WAS have significant potential for converting the greenhouse gas CO2 into the fuel methane. Methane production was found to increase 70 fold by active methanogens in the enriched methanogens culture after 3 days in the presence of H2 and CO2 . Throughout the process, CO2 was completely consumed after 4 days of incubation in the vials after sparging with a mixture of H2 and CO2, resulting in significant biological CO2 sequestration by methanogens. Using a mixture of H2 and 13 CO2, we also demonstrated that the methane produced is due to the utilization of CO2 . Microbial community studies via by quantitative real time PCR (qRT-PCR) indicate the dominance of archaea in the enriched methanogens culture of WAS. Archaeal community studies of the enriched methanogens via high-throughput 16S rRNA sequencing also showed that the archaea consist mainly of hydrogenotrophic and aceticlastic methanogens such as Methanobacteriaceae, Methanospirillaceae and Methanosarcinaceae spp. which are actively grown in H2 and CO2 . We envision that CO2 gas from power plants can be directed to enriched methanogens of WAS to prevent release of this greenhouse gas while generating a useful biofuel (methane) or other valuable products using this single carbon atom.